Ecological patches to recover the evolutionary cultural landscape of the Barranco Tumino of Moyobamba, Peru - Urbina Lavajos, Camila (2025)
The study addresses the deterioration of the evolving cultural landscape of the Barranco Tumino in Moyobamba, Peru, caused by inappropriate land use and factors derived from the informal settlement of the population. Using a qualitative and descriptive approach, the current state of the ravine was characterized, the levels of deterioration of its landscape units were identified, and restoration strategies were designed. The results indicated that 41% of the area is under conservation, while 41% faces unsustainable uses such as dumps and drainage. In addition, landscape fragmentation was observed, affecting ecological connectivity and biodiversity. In response, a system of ecological patches was proposed, including the creation of urban gardens, green corridors, trails, boardwalks, viewpoints, wetlands and urban lagoons. These measures seek to preserve biodiversity, enhance the natural environment and strengthen the landscape's capacity to adapt to environmental pressures, ensuring its long-term sustainability.